Implementasi Akad Isthisna’ Tanpa Bank Dalam Memenangkan Persaingan Bisnis Property (Studi Kasus di PT Samawa Proper - Alvan fathony; Ahmad Nur Bustomi (Universitas Muhammadiyah Sidoarjo, 2021)
The house is one of the needs that must be fulfilled by humans, the need for housing in Indonesia is increasing every year in line with the high population growth. Based on a letter issued by the finance minister regarding the home ownership loan program, many residential property business developers offer home services in an effort to meet the need for housing. Then came the conventional mortgages and sharia mortgages. Sharia mortgages are schemes that continue to develop and attract public interest with their sharia transaction systems, either with a Murabaha or Isthisna 'contract. This study aims to find out how the practice of istishna contract is applied by the developer of PT Samawa Property Group. This type of research is descriptive qualitative research with exposure related to solving existing problems. The results of this study indicate that the contract used is the istishna contract which is able to meet the needs of the community for houses without riba transactions, clear price transparency, no fines or confiscation so that it is mutually beneficial and able to improve the welfare of the community.